Impact of DSSS in LTE link-level modelling / A. E. Azhar, A. L. Yusof and A. Idris - Azhar, A. E.; Yusof, A. L.; Idris, A. (UiTM Press, 2018)
Long Term Evolution (LTE) system has higher PAPR value at OFDM Downlink. The 3GPP standard stated that PAPR of LTE OFDM is 12dB. There are various interference management methods have been proposed to improve PAPR performance and most known methods are clipping and filtering. In this work, we proposed DSSS in LTE link-level system. The DSSS is added before Modulator at LTE Transmitter and after Modulator at LTE Receiver. The proposed LTE link-level system is investigated on PAPR and BER performance. The results gave 8.333% of PAPR improvement compare to LTE original and BER performance has robustness against errors.